The Productivity of Non-AGP Broiler Small-Holder Businesses Based on Production, Economy and Social Demography - Japutra, Bambang Rijanto; Ismoyowati, Ismoyowati; Setianto, Novie Andri (ANIMAL PRODUCTION, 2021)
The study investigated the productivity of smallholder broiler farming with and without AGP to identify the difference between the utilization and absence of antibiotic growth promoter (AGP) incorporated into the broiler feed based on production (feed efficiency and cumulative performance index), economy (farming capacity and income), and socio-demography (farmers’ education background, age, farming experience, and farming motivation) in Central Java Province. The study was conducted through a survey of broiler farmers in one partnership company. The data analysis included analysis of variance based on a stratified GLM (general linear model) and correlation analysis. The result did not identify significant differences in the production aspects in either AGP or non-AGP farming, among different regencies, and farm size. In 2018, when farms stop using the AGP, the farm production is better than in 2017 when the AGP was used. Based on the economic aspect, the AGP and non-AGP administration did not affect farming capacity and income. The socio-demographic aspect showed that education significantly affected the success of broiler farming, while farmers’ age, farming experience, and farming motivation did not affect the production of broiler farming. The result of correlation analysis showed that education background contributed to feeding efficiency and cumulative performance index. The conclusions are (1) broilers fed with either AGP or non-AGP containing feed showed relatively similar performance, (2) the government policy on the prohibition of AGP does not contribute to the decrease of farmers’ income and (3) the demographic aspect affecting the success of the broiler farming business is the farmers’ education level.